KINERJA PELAYANAN PUBLIK DESA CATURTUNGGAL KECAMATAN DEPOK KABUPATEN SLEMAN - Fuad Nurcahyo; Moh. Mahsun (Jurnal Riset Mahasiswa, 2023)
Research on the performance of publik service officers at the Caturtunggal Village Government with the aim of reviewing aspects of human resource competence and the Decree of the Minister of State Apparatus Empowerment Number 63 of 2003 on measuring the performance of publik service officers of the Caturtunggal Village Government based on productivity, publik service orientation, responsiveness, responsibility and accountability. The research method used is quantitative by describing the performance of publik service officers in the Caturtunggal village government, Depok District, Sleman Regency. The results of the research on measuring the performance of the publik service apparatus of the Caturtunggal Village Government by using a percentage index on the factors that affect performance are Publik Service Productivity of 86.00% with Very Good criteria, Publik Service Orientation of 85.38% with Very Good criteria, Responsiveness of 84.84% with Very Good criteria Good, Responsibility is 84.38% with Very Good criteria and Accountability is 81.41% with Good criteria. The overall performance of the apparatus is 85.16% with very good criteria. The review of aspects of human resource competence in the performance of publik service officers of the Caturtunggal Village Government are as follows: financial aspects, community satisfaction aspects, apparatus satisfaction aspects, stakeholder satisfaction aspects and time aspects. Review of service standards of service personnel in accordance with the Decree of the Minister of Administrative Reform No. 63 of 2003 on publik services with the dimensions of Service Procedures being good, Completion Time is good enough, Details of Service Costs are good, Facilities and Infrastructure are adequate, Competence of Service Providers is maximized and adequate. Penelitian pada kinerja aparat layanan publik pada Pemerintah Desa Caturtunggal dengan tujuan untuk tinjauan aspek kompentensi sumber daya manusia dan Keputusan Menteri Pendayaagunaan Apartur Negera Nomor 63 Tahun 2003 pada pengukuran kinerja aparat layanan publik Pemerintahan Desa Caturtunggal dengan berdasarkan produktivitas, orientasi pelayanan publik, responsivitas, responbilitas dan akuntabilitas. Metode penelitian yang digunakan adalah kuantitatif dengan mendiskripsikan kinerja aparat layanan publik yang terdapat pada pemerintah desa Caturtunggal Kecamatan Depok Kabupaten Sleman. Hasil penelitian pengukuran kinerja aparat layanan publik Pemerintah Desa Caturtunggal dengan menggunakan indeks presentase pada faktor-faktor yang mempengaruhi keinerja adalah Produktivitas Layanan Publik sebesar 86.00% dengan kriteria Sangat Baik, Orientasi Pelayanan Publik sebesar 85.38% dengan kriteria Sangat Baik, Responsivitas sebesar 84.84% dengan kriteria Sangat Baik, Responbilitas sebesar 84.38% dengan kriteria Sangat Baik dan Akuntabilitas sebesar 81.41% dengan kriteria Baik. Kinerja aparat secara keseluruhan sebesar 85.16% dengan kriteria Sangat Baik. Tinjauan aspek pada kompetensi sumber daya manusia dalam kinerja aparat layanan publik Pemerintah Desa Caturtunggal adalah berikut: Aspek finansial, Aspek kepuasan masyarakat, Aspek kepuasan aparat, Aspek kepuasan stakeholder dan Aspek waktu. Tinjauan standar layanan aparat layanan sesuai dengan Keputusan Menteri Pendayaagunaan Apartur Negera Nomor 63 Tahun 2003 pada pelayanan publik dengan dimensi Prosedur Pelayanan sudah baik, Waktu Penyelesaian sudah cukup baik, Rincian Biaya Pelayanan sudah baik, Sarana dan Prasarana sudah memadai, Kompetensi Petugas Pemberi Pelayanan sudah maksimal dan memadai.